The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1055/s-0041-1736163
|View full text |Cite
|
Sign up to set email alerts
|

Follicular Cholecystitis Mimicking Xanthogranulomatous Cholecystitis and Malignancy: A Case Report

Abstract: Chronic follicular cholecystitis (CFC) is a rare pathology characterized by prominent lymphoid follicles in the lamina propria distributed throughout the gallbladder wall. It has also been mentioned in the literature as lymphoid hyperplasia and pseudolymphoma. CFC represents less than 2% of cholecystectomies. Its etiopathology is mostly unknown. Most reports are based on histopathological findings, with little or no imaging analysis. We describe a case involving a 66-year-old man radiologically diagnosed as xa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Xanthogranulomatous cholecystitis is a rare variety of chronic cholecystitis 2 , 6 , 8 . XGC is a benign but occasionally aggressive disorder resulting from chronic inflammation of the gallbladder wall 1 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Xanthogranulomatous cholecystitis is a rare variety of chronic cholecystitis 2 , 6 , 8 . XGC is a benign but occasionally aggressive disorder resulting from chronic inflammation of the gallbladder wall 1 .…”
Section: Discussionmentioning
confidence: 99%
“…Radical cholecystectomy is performed involving en bloc resection of segments IVB and V of the liver when malignancy is suspected 4 . Intraoperative frozen section analysis can be done to differentiate the differential diagnoses 6 , 8 . The postoperative mortality rate and complications are relatively low 4 .…”
Section: Discussionmentioning
confidence: 99%
“…FC is a rare diagnosis and has not been well described in the literature [4] . Differential diagnoses of FC include primary MALT lymphoma of the gallbladder, xanthogranulomatous cholecystitis, and gallbladder carcinoma [5] , [6] .…”
Section: Clinical Discussionmentioning
confidence: 99%
“…In GBC patients with p53 overexpression, the 5-year survival rate was 17.2 25 . Ki-67: In a study it was concluded that expression of Ki-67 had a worse postoperative prognosis 26 . Combining various immune markers together for diagnostic purpose led to the highest levels of sensitivity and specificity.…”
Section: Introductionmentioning
confidence: 99%